2010
DOI: 10.21608/eajbsa.2010.15204
|View full text |Cite
|
Sign up to set email alerts
|

Degree-days units and expected generation numbers of peach fruit fly Bactrocera zonata (Saunders) (Diptera: Tephritidae) under climate change in

Abstract: Climate change could profoundly affect the status of agricultural insect pests. This study predicts expected peach fruit fly (PFF) annual generations under current and future climate by using the accumulated thermal heat units expressed as degreedays unit (DDU). We evaluated how temperature expected to influence the annual generation numbers in three governorates of Egypt using the climate change data output from the HadCM3 model for A1 scenarios proposed by the Intergovernmental Panel on Climate Change. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It has over 500 genera represented by about 4000 species distributed throughout the temperate, subtropical and tropical areas of the world (Christenson & Foote 1960;Abdullah 2008;Rattanapun 2009;Khalil et al 2010;Mosleh et al 2011;El-Gendy 2012). With few exceptions, most of fruit flies are polyphagous in nature with considerable diverse host range, usually feeding on closely related hosts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has over 500 genera represented by about 4000 species distributed throughout the temperate, subtropical and tropical areas of the world (Christenson & Foote 1960;Abdullah 2008;Rattanapun 2009;Khalil et al 2010;Mosleh et al 2011;El-Gendy 2012). With few exceptions, most of fruit flies are polyphagous in nature with considerable diverse host range, usually feeding on closely related hosts.…”
Section: Introductionmentioning
confidence: 99%
“…This pest was recorded on more than 50 cultivated and wild plant species, mainly those with fleshy fruits (White & Elson-Harris 1992;Khalil et al 2010). Infestation not only cause severe damage by reducing both fruit production and quality, but also impede exportation of fresh fruits due to the quarantine restrictions (Chen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of more number of generations annually with extreme temperatures in case of majority of insect species was well known and this phenomenon becomes regular with gradual warming (Lastuka, 2008) and our results add S. litura on peanut in India to the list as a case in point. The information on occurrence of additional generations with increase in temperature was well documented across various insect orders viz; lepidopterans -Nephotettix cincticeps (Yamamura et al, 2006), Plutella xylostella, (Kiritani, 2006), Cydia pomonella (Marchioro and Foerster, 2011;Hirschi et al, 2012), Phthorimaea operculella (Abolmaaty et al, 2011) and other orders (Khalil et al, 2010;Hlasny et al, 2011). It was found that a substantial proportion of the 263 multivoltine lepidopteran species in his dataset exhibited an increased frequency of second and subsequent generations since 1980, with 44 species displaying a stable increase in the number of generations after 1980 (Altermatt, 2010).…”
Section: Mean Number Of Generations and Generation Timementioning
confidence: 99%
“…It has over 500 genera represented by about 4000 species distributed throughout the temperate, subtropical and tropical areas of the world (Rattanapun 2009;Khalil et al 2010;Mosleh et al 2011;El-Gendy 2012). Among the various species of tephritid flies, the peach fruit fly (PFF), Bactrocera zonata (Saunders), is an extremely aggressive pest infesting some of the main commercial fruit and vegetables (Amin 2003;White & Elson-Harris 1992).…”
Section: Introductionmentioning
confidence: 99%